Hypersensitivity to azathioprine in myasthenia gravis. - Watts, G. F. (BMJ Group, 1984)
A patient with myasthenia gravis is described who exhibited hypersensitivity including an apparent acute exacerbation of the underlying disorder when treated with azathioprine. 6-mercaptoprine (6-MP) also produced hypersensitivity which, in contrast, did not manifest as a myasthenic exacerbation.